Slower economic growth affects the 1995 labor market. - Gardner, Jennifer M.; Hayghe, Howard V. (Monthly Labor Review, 1996)
As the pace of U.S. economic activity moderated in 1995, job growth slowed dramatically. Nevertheless, it was sufficient to absorb the small increase in the supply of labor, with the result that the unemployment rate remained at approximately the same level it had reached by the end of 1994. Employment grew at a brisk pace in the first quarter of 1995, but job gains declined sharply as the economy started to slow. Employment growth continued at a much more moderate rate for the rest of the year, so that almost 1.9 million jobs had been added to America's payrolls by the fourth quarter. This was a significantly smaller number of jobs than in each of the preceding two years. Most of 1995's job gains were in the services industry sector. Manufacturing employment began to decline in the spring of 1995, however, and by the end of the year that sector had lost almost a quarter of a million jobs.